Двое под солнцем: роман / Татьяна Тронина - Тронина Татьяна Михайловна (Эксмо, 2022)
Экземпляры: ЦБ (20230529) / Инвентарный номер: 59765 / Цена: 283.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Т 73 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44